REGULATION, CENSORSHIP AND MEDIA FREEDOM - Oyinloye, Oloyede; Oyegoke, Nathaniel Adeoye; Odion, Victor Ebenezer; Ojewumi, Oluwaranti Olufunke (African Journal of Social and Behavioural Sciences, 2024)
This study delves into the complex interplay of regulation, censorship, and media freedom within Nigeria, exploring their implications for democratic governance and societal development. It aims to understand how regulatory inconsistencies, government censorship practices, and the proliferation of misinformation on digital platforms impact media freedom and democratic discourse. This research work discovered how regulatory inconsistencies and government censorship practices, such as the Cybercrime Act and the arbitrary suspension of social media platforms, hinder freedom of expression and access to information. The research however adopts a comprehensive approach, combining a thorough review of existing literature, empirical studies, and case analyses. It also employs both qualitative and quantitative methods to analyse legal frameworks, media ownership structures, and freedom of expression indicators. Surveys and interviews are conducted to gauge journalists’ perceptions of government interference and censorship, as well as the impact on media pluralism and independence. The primary findings highlight significant challenges to media freedom and democratic governance in Nigeria.